Analisis Persepsi Kemudahan dengan Penggunaan Catatan Medis Berbasis Elektronik (RME) pada Rumah Sakit Menggunakan Pendekatan Technology Acceptance Model (TAM) - Petra Sunggul Morenfino; Hosizah Markam; Mieke Nuermalasari; Witri Zuama Qomarania (TIN: Terapan Informatika Nusantara, 2026)
The purpose of this study was to analyze the relationship between perceived ease of use and the use of Electronic Medical Records (EMR) through the Technology Acceptance Model (TAM) approach. This study was conducted in July 2025 at RSUP Fatmawati using a quantitative approach with a cross-sectional design. The research sample involved 104 healthcare workers who utilized Electronic Medical Records (EMR). The sampling technique applied was random sampling using the Simple Random Sampling method. Data were collected through a questionnaire using a 1–4 Likert scale.The results indicated that the level of Electronic Medical Record (EMR) usage at Fatmawati General Hospital was categorized as high (index 91.13), showing that healthcare workers had routinely used EMR in daily services and had a high level of familiarity (90.16). Perceived ease of use was also in the high category (82.62), where the system was considered easy to learn, operate, and supportive of work effectiveness. Although the level of RME use is generally in the high category, initial observations indicate that there are still some health workers who experience difficulties in understanding and operating the system optimally. The Spearman Rank test results indicated a positive, significant, and strong relationship between perceived ease of use and EMR usage (r = 0.706; p < 0.05). This implies that the higher the perceived ease of use, the higher the EMR usage, making ease of use a crucial factor in the successful implementation of the system. It is recommended that hospitals continuously improve the quality of the EMR system to remain user-friendly, accompanied by regular training and adequate technical support. These efforts are expected to enhance healthcare workers’ perceived ease of use, thereby making EMR utilization more effective. The contribution of this study is to provide empirical evidence regarding the importance of perceived ease of use as a crucial factor influencing the utilization of Electronic Medical Records (EMRs) in a government hospital serving as a national referral center. The findings of this research are expected to serve as a reference for hospital decision-makers in improving system interface quality, enhancing user training, and developing implementation approaches for Electronic Medical Records (EMRs) that are focused on the needs of healthcare professionals.